Implementation of Indoor 4G Signal Interference Detection using USRP B210 and RTL-SDR - Ciksadan, Ciksadan; Thabroni, Feri; Suroso, Suroso (Sistemasi: Jurnal Sistem Informasi, 2025)
Signal interference is one of the main challenges in maintaining the quality of 4G network services, particularly in indoor environments with complex propagation characteristics. This study aims to develop a 4G signal interference detection system based on Software Defined Radio (SDR), utilizing a USRP B210 device as the transmitter and two RTL-SDR units as receivers. The system is designed to monitor signals in real time at frequencies of 800 MHz and 1700 MHz, and to analyze Received Signal Strength Indicator (RSSI) and Signal-to-Noise Ratio (SNR) parameters from each RTL-SDR to identify potential signal interference. The test results show that RTL1 consistently received signals of higher quality compared to RTL2. At 800 MHz, the SNR difference between the two receivers reached 21.06 dB, while at 1700 MHz it was 15.46 dB. Although no foreign signals were visually detected in the spectrum, the significantly lower SNR values on RTL2 indicate the presence of non-spectral interference, likely caused by differences in propagation conditions such as multipath effects or physical obstructions. These findings demonstrate that the proposed system is capable of detecting hidden interference through a quantitative comparison between two receivers operating simultaneously. This approach proves effective for indoor signal monitoring and can be further developed to support automation using machine learning techniques.